2016
DOI: 10.1371/journal.ppat.1006082
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Correlates with the Number of Herpes Viral Genomes Initiating Infection in Single Cells

Abstract: Viral gene expression varies significantly among genetically identical cells. The sources of these variations are not well understood and have been suggested to involve both deterministic host differences and stochastic viral host interactions. For herpesviruses, only a limited number of incoming viral genomes initiate expression and replication in each infected cell. To elucidate the effect of this limited number of productively infecting genomes on viral gene expression in single cells, we constructed a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…Conversely, we found that the fraction of host cell mRNAs was decreased in high-yield cells. This was similarly observed for herpes virus-infected single cells [63]. Here, a higher cellular gene expression coincided with lower viral gene expression.…”
Section: Discussionsupporting
confidence: 79%
“…Conversely, we found that the fraction of host cell mRNAs was decreased in high-yield cells. This was similarly observed for herpes virus-infected single cells [63]. Here, a higher cellular gene expression coincided with lower viral gene expression.…”
Section: Discussionsupporting
confidence: 79%
“…Thus while there is a distinct genome decompaction after nuclear import, this is constrained in a relatively regular manner. The distribution of the numbers of genomes appearing in the nucleus and the relationship to moi bear similarity to those from physical analysis of adenovirus genome entry [16] and are relevant also to conclusions from other studies on the numbers of herpesvirus nuclear genomes that participate in transcription and replication [61][62][63]. We observed that at a standard moi of 10 pfu/cell (100-200 particles coating a cell), although a small percentage of nuclei could contain relatively high numbers, the mean numbers of nuclear genome foci was approximately 5 and around 90% of cells had fewer than 10.…”
Section: Hsv Genome Entrymentioning
confidence: 58%
“…A later study measured the burst size from individual HeLa cells infected 32 with Herpes Simplex virus 1 (HSV-1) and found that many of the infected cells did not release any progeny, 33 that the variability between individual cells was high and that it did not correlate with the multiplicity of 34 infection (MOI) used (Wildy et al, 1959). More One well-known source of this variability is the random distribution of the number of viruses that individual 39 cells encounter (Parker, 1938;Smith, 1968;Cohen and Kobiler, 2016). Another source is genetic variability 40 in the virus population, with some virus particles being unable or less fit to establish infection (Huang and 41 Baltimore, 1970; Lauring et al, 2013;Stern et al, 2014).…”
Section: Introduction 25 26mentioning
confidence: 99%